1987
DOI: 10.1037/0003-066x.42.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Survey of expert opinion on intelligence and aptitude testing.

Abstract: Psychologists and educational specialists with expertise in areas related to intelligence testing responded to a questionnaire dealing with a wide variety of issues constituting the IQ controversy. Overall, experts hold positive attitudes about the validity and usefulness of intelligence and aptitude tests. Tests are seen as adequately measuring most important elements of intelligence, although the tests are believed to be somewhat racially and socioeconomically biased. There is overwhelming support for a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
7

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(106 citation statements)
references
References 16 publications
2
97
0
7
Order By: Relevance
“…Future studies are needed to identify the traits that determine effort on low-stakes tests. More than 1,000 psychologists and educational specialists with expertise in intelligence testing rated the importance of six "personal characteristics" to performance on intelligence tests (46). (47) found that individuals higher in achievement motivation tend to think longer and are less sensitive to financial incentives when answering questions on an untimed intelligence test.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to identify the traits that determine effort on low-stakes tests. More than 1,000 psychologists and educational specialists with expertise in intelligence testing rated the importance of six "personal characteristics" to performance on intelligence tests (46). (47) found that individuals higher in achievement motivation tend to think longer and are less sensitive to financial incentives when answering questions on an untimed intelligence test.…”
Section: Discussionmentioning
confidence: 99%
“…), more of the highly convincing items are G rather than E" (p. 319). The survey of over 1,000 experts in behavioral genetics and psychometrics by Snyderman and Rothman (1987) also found that a plurality believed the Black-White IQ difference "to be a product of both genetic and environmental variation" (p. 141). However, there are also notable statements to the contrary.…”
Section: Section 14: Progressive Research Leads To Provisional Truthmentioning
confidence: 99%
“…His conclusions, the theoretical issues they raised, and the public policy recommendations that many saw as stemming directly from them were dubbed "Jensenism," a term which entered the dictionary. Since 1969, Jensen has continued to publish prolifically on all of these issues, and increasing numbers of psychometricians and behavioral geneticists have come to agree with one or more of the tenets of Jensenism (Snyderman & Rothman, 1987.…”
Section: Section 1: Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the idea that genetics influences behavior went through a period of controversy, particularly with respect to race and intelligence, it is currently enjoying a new, high level of acceptance (Plomin & Rende, 1991). For example, most social scientists now believe that intelligence test scores are significantly affected by genetics (Snyderman & Rothman, 1987).…”
Section: Introductionmentioning
confidence: 99%